Competency and satisfaction level of high and medium fidelity simulation in drug administration teaching and learning practice: A comparative study - Nurumal, Mohd. Said; Haji Hashim, Ummu Hanani; Aung, Khin Thandar (Official Publication of Chandramma Education Society, 2017)
Background: Nowadays, the simulation practice is becoming more popular in nursing education and that can improve the nursing students’ clinical skills and soft skills. Moreover, it allows the students from conductive simulated environment to the real-like situation that they may experience later in their clinical attachment period. Due to little current information of issues pertaining to the relevant type of simulation that is able to create the students’ competency and satisfaction, therefore, a thorough comparison between the effectiveness of high fidelity and medium fidelity simulation is needed. Objective: The aim of this study was to compare the effectiveness of medium and high fidelity simulation towards developing student’s competency skill in drug administration via oral, subcutaneous, intramuscular and intravenous route and also to identify the student’s satisfaction level towards high and medium fidelity simulation. Methods: A comparative cross-sectional study was conducted in Kulliyyah of Nursing, International Islamic University Malaysia (IIUM) at Jalan Hospital Campus, Kuantan. First year nursing students who match including criteria were recruited as a compulsory class (N= 54) and the students were divided into two groups using simple random assignment sampling. The students were assessed during the simulation using rubric checklist and completed Likert scale after finished each simulation sessions. Data analysis involved Wilcoxon signed rank test using PASW Statistic 18. Results: The findings on the competency level (technical skills and non-technical skills) showed statistical significant improvement of mean score (p< 0.05) in high fidelity simulation compared to medium fidelity simulation in both groups. The students’ satisfaction levels towards simulation were significant increased statistically for both groups (p< 0.05) in second session of simulation regardless of the type fidelity simulation. Conclusion: The high fidelity simulation was able to prepare better technical and non-technical skills as compared to medium fidelity simulation. However, the students’ satisfaction did not associate with the type of fidelity simulation but showed improvement after repeated or sequential simulation. More research is required to compare and to explore more about the simulation fidelity.